Analysis Customer Segmentation on Individual Life Insurance in Kalimantan Province Using K-Means Clustering with SPSS - Nur Aulia, Reza; Taufiqillah, Rizal; Dewi, Puspita (Universitas Pahlawan Tuanku Tambusai, 2024)
The Indonesian life insurance industry has witnessed remarkable growth in recent years, fueled by a rising awareness among the populace regarding the significance of safeguarding oneself and their families. However, the industry also faces a multitude of challenges, including intense competition, low market penetration, and evolving consumer behavior. Customer segmentation emerges as a crucial strategy to address these challenges effectively. Market segmentation holds immense value as it empowers companies to tailor their products and services to specific customer groups. Implementing K-Means Clustering to categorize life insurance customers based on their profiles and behaviors proves to be an effective approach for developing a successful marketing strategy. Understanding the profiles and behaviors of life insurance customers can serve as a powerful tool for attracting new customers. This case study delves into the practices of a prominent life insurance company in Indonesia, referred to as PT. XYZ to maintain data privacy. Customer data was extracted from the company's internal database in April 2024, and the analysis focused exclusively on customers in Kalimantan Island. The study's findings reveal significant differences in characteristics and preferences among the three identified customer segments. Life insurance products emerged as the most sought-after across all segments. While the Agency channel dominated in all segments, Bancassurance also held a notable market share. Bundling life insurance products with additional accident insurance benefits presents a compelling value proposition. Expanding hospital coverage to encompass the ASEAN region can further enhance the value proposition. The 7P framework serves as a valuable tool for achieving the company's strategic objectives.